Fisheries Management in the Black Sea—Pros and Cons - Raykov, Violin S.; Duzgunes, Ertug (Frontiers in Marine Science, 2017)
In Black Sea the term ”management” usually is interpreted as series of regulatory measures introduction in the fishery practice with no doubt, positive influence on the general condition of marine living resources. On the other hand, similar restrictions could not lead conceptually to the “management policy” if they are not systematized with clearly formulated aims and prerogatives. In the presence of introduced “closed area”, ”closed season”, ”minimum mesh size” and other regulations, altogether all of these measures could not serve as restrictions over the yield capacity, i.e. could not influence the fishing effort. The main priority in such a conception is a precautionary approach and responsible fishery practice in force. It could “work” properly with quota principle implementation, together with more effective system control. It is hard for the any single country to follow these regulations and it is harder for all Black Sea countries to do so, because they are exploiting resources from shared fish stocks. In order to have an effective management on these stocks, joint stock assessments are needed. On this basis, the allocation of the catches for the separate Black Sea country could be established. Unfortunately, due to the different reasons, for the time being this is impossible. Hence, it could be assumed that management of the marine living resources shall be fulfilled in its incomplete form, under the national jurisdiction prescript, as they are.